Crises in clinical care: an approach to management. Issue 3 (2nd June 2005) - Runciman, W B; Merry, A F
Abstract : A "crisis" in health care is "the point in the course of a disease at which a decisive change occurs, leading either to recovery or to death". The daunting challenges faced by clinicians when confronted with a crisis are illustrated by a tragic case in which a teenage boy died after a minor surgical procedure. Crises are challenging for reasons which include: presentation with non-specific signs or symptoms, interaction of complex factors, progressive evolution, new situations, "revenge effects", inadequate assistance, and time constraints. In crises, clinicians often experience anxiety- and overload-induced performance degradation, tend to use "frequency gambling", run out of "rules" and have to work from first principles, and are prone to "confirmation bias". The effective management of crises requires formal training, usually simulator-based, and ideally in the inter-professional groups who will need to function as a team. "COVER ABCD–A SWIFT CHECK" is a precompiled algorithm which can be applied quickly and effectively to facilitate a systematic and effective response to the wide range of potentially lethal problems which may occur suddenly in anaesthesia. A set of 25 articles describing additional precompiled responses collated into a manual for the management of any crisis under anaesthesia has been published electronically as companion papers to this article. This approach to crisis management should be applied to other areas of clinical medicine as well as anaesthesia.